Fractal dimension of large aggregates under different flocculation conditions - Moruzzi, Rodrigo B. [UNESP]; de Oliveira, André L. [UNESP]; da Conceição, Fabiano T. [UNESP]; Gregory, John; Campos, Luiza C. (Elsevier, 2017)
The two-dimensional fractal dimension (Df) of large aggregates of kaolin (> 540 μm) during the shear flocculation process for kaolin solution was investigated using non-intrusive in situ image-based acquisition system. Separate experiments were also carried out for three different sized sub-ranges of large aggregates (0.540–1.125 mm; 1.125–1.750 mm; 1.750–2.375 mm). Digital images were taken at a frequency of 10 Hz for 10 s for each different pairs of gradients of velocity (Gf) of 20 and 60 s− 1 and flocculation times of 2; 3; 4; 5; 10; 20; 30; 60; 120 and 180 min. For the same conditions, particle size distribution (PSD) was also determined. Under the investigated conditions, the lowest Gf produced the greatest Df (1.69) at a flocculation time of 30 min for the whole range of aggregates. Also, the evolution of the longest length of aggregate (l) and Df with time, showed that the dynamic steady-state was reached at different times for each shear rate and l ranges. However, Df varied for each size sub-range (ca. 1.1 to 1.8). Finally, the behavior of the aggregate structure may be understood by the predominance of different aggregation mechanisms such as cluster-cluster for Gf of 60 s− 1 and particle-cluster for Gf of 20 s− 1.
Keywords: Aggregates; Flocculation; Fractal dimension; Shear rate